Perlindungan Hukum Terhadap Perusahaan Pelayaran Atas Wanprestasi Pencarter dalam Perjanjian Pengangkutan (Mimbar Keadilan, 2023)
Shipping companies are one of the parties that are vulnerable to becoming victims of default in a charter party agreement, thus in practice shipping companies as carriers always apply clauses of retention rights and sell cargo clauses in their charter party agreement. This research is a follow-up to earlier research that has discovered that charterers often commit acts of default, where this research focuses on legal protection for shipping companies in the event of default by charterers. This research is qualitative research using normative juridical research methods based on laws and case approach. A Charter party agreement is a legal relationship between the carrier and the charterer where the carrier binds himself to organize the transportation, nn the other hand the charterer binds himself to make payments. By the act of default committed by Bintang Sarana Laut, Co. Ltd. (charterer), Bendera Bahtera Kemenangan, Co. Ltd. (carrier) can terminate the agreement unilaterally without prejudice to their rights to demand reimbursement of costs, compensation, and interest. The law also gives the rights to Bendera Bahtera Kemenangan, Co. Ltd. to request guarantee before the cargo is delivered to Bintang Sarana Laut, Co. Ltd. But if Bintang Sarana Laut, Co. Ltd. doesn’t wish to provide any guarantee, Bendera Bahtera Kemenangan, Co. Ltd. can store the cargo and may file a lawsuit against Bintang Sarana Laut, Co. Ltd. and make a request to the court to give power for Bendera Bahtera Kemenangan, Co. Ltd. to sell the cargo as payment for charter and storgae fees. The method used by Bendera Bahtera Kemenangan, Co. Ltd. in resolving the default disputes in the charter party agreement is through a consensus deliberation mechanism.